Do Women in Leadership Reduce Sexual Harassment Claims on College Campuses?. Issue 2 (3rd May 2020) - Glass, Christy; Cook, Alison; Pierce, Brandon
Abstract : This article analyzes whether the representation of women in leadership roles reduces sexual harassment claims on college campuses. We test competing claims regarding the impact of women's workplace authority on sexual harassment. Our framework draws on the women as agents of change and power paradox perspectives to interrogate the role of gender and power in reducing workplace harassment in institutions of higher education. We find that women's overall integration into upper administrative positions reduces harassment claims. However, we also find that the gender of the president and the Title IX officer is not significantly related to the number of harassment claims. We consider the implications of these findings for ongoing efforts to reduce harassment on college and university campuses.